ISOLASI, UJI AKTIVITAS, DAN OPTIMASI INHIBITOR α-AMILASE ISOLAT KAPANG ENDOFIT TANAMAN BINAHONG (Anredera cordifolia) (Ten.) Steenis - Diani Ajeng Prahesti; Sri Pujiyanto; MG Isworo Rukmi (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2018)
Diabetes mellitus (DM) is a hyperglycemia disease caused by insensitivity of cells to insulin that causes the presence of glucose in blood and urine. The α-amylase inhibitors is a compound that inhibit carbohydrates breakdown into glucose by amylase enzyme. Binahong (Anredera cordifolia) has been used by Indonesian people since long time ago to treat various diseases such as for anti-diabetic. The aims of study were to obtained the endophytic fungal isolated from Binahong plant, and find out of their ability of α-amylase inhibitor activity by treatment of carbon source and pH of production medium. The isolating endophytic fungal from binahong roots, stems, and leaves in medium PDA. The α-amylase inhibitory test was using starch substrate and the α-amylase inhibitory measure using spectrophotometric method. The study was used one factor CRD i.e. carbon source including sucrose, lactose, and maltose. The best carbon source then continued to test with variation pH 5,6, and 7. The data obtained were then analyzed by Analysis of Variance (ANOVA). Five endophytic fungal isolated from binahong were only one isolated i.e DT should high potensial in inhibiting α-amylase 91,43%. The best carbon source for inhibitory α-amylase i.e sucrose with the percentage of 58,91%, while pH 5 is the best pH medium production continous treatment carbon source sucrose with the percentage 37,83%. The result of statistical test showed that sucrose as the best carbon source just than lactose and maltose, and pH 5 as the best medium pH for the production α-amylase inhibitor. Key words : α-amylase inhibitor, endophyte fungi, Anredera cordifolia, diabetes mellitus